E-Module Math O_Pedia: A Digital Learning Innovation for Elementary Students' Understanding of Fractions - Heni Ria Yunita; Roemintoyo Roemintoyo; Moh Salimi (Universitas Pendidikan Ganesha, 2025)
Fractions are one of the materials that are quite difficult to understand. Efforts made to overcome this problem through the development of learning resources in the form of E-Module Math O_Pedia. This study aims to develop E-Module Math O_Pedia as a digital learning innovation for understanding fractional numbers in elementary school students. The research method uses Research and Development (R&D) using the ADDIE model. The product trial design consists of an initial trial stage. The data collection instruments used were interviews, observations, questionnaires, a feasibility scale by material experts, a feasibility scale by media experts, and a feasibility scale by language experts, as well as a student response scale. The research subjects were 20 3rd grade elementary school students. Data analysis used the Miles & Huberman technique. The research findings showed that the material aspect was in the very good category with a score of 92; the media aspect was in the very good category with a score of 92, and the language aspect was in the very good category with a score of 96; while the feasibility of the e-module on the user response factor showed that the product was classified as a very feasible category. The results of the study concluded that the E-Module Math O_Pedia was very good and quite effective in improving students' understanding of fractional number material.